PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUKSI DARI KERTAS KORAN BEKAS SISWA KELAS IV SDN 003 TANJUNG KECAMATAN KOTO KAMPAR HULU - Putrapi, Anren Putrapi; Marhadi, Hendri Marhadi; ', Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : Problem in this research is still its doily skill of student in study of art in course of study of teacher still use the way of conventional, that is: student less involved in study process, more teacher use discourse method, even do not use study model, learn only from teaching materials or teacher, process its his its heedless study empirically student, so that mentioned cause student keterampilam become to lower. Pursuant to the problems hence require to look for by its resolving road;street by using hand in glove model of its bearing empirically student in everyday life, and all important can make atmosphere learn productive and creative. Subjek in this research is class student of IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu with amount of student 19 people. This research is done conducted in two cycle, cycle of I executed by thrice cycle and meeting of II is also done conducted by thrice meeting. Instrument data collecting at this research is observation sheet learn and student. This research in the form of Research Of Action Class ( PTK), this research aim to to increase skill make class student construction object of IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu. Result of this research of menunjukan that strategy study of kreatif-produktif can uplift skill student in making construction object. This matter can be seen from average value which increasing. At elementary score of mean assess student that is 57,32 and at cycle of I become 66,23 experiencing of the make-up of with difference 8,91 poin. While mean result of learning student at cycle of II that is 76,61 experiencing of the make-up of with difference 10,38 poin. This of its meaning of strategy study of kreatif-produktif can uplift skill to make object of kontruksi of newspaper paper of is ex- class student IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu. Keyword : Creative Strategy Study - Productive, Skill, Object Construction